Effects of microencapsulated carvacrol and cinnamaldehyde on feed digestibility, intestinal mucosa, and biochemical and antioxidant parameters in broilers - Facchi C.S. (2023)
© This is an open access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly citedThe objective of this study was to evaluate the effects of different levels of microencapsulated carvacrol and cinnamaldehyde on metabolizable energy, feed digestibility, intestinal morphometric analysis, and antioxidant parameters in broilers. A completely randomized design with five treatments and eight replications of eight broilers (Cobb male) was used, and collections were carried out at 20 and 42 days of age. Carvacrol and cinnamaldehyde concentrations (mg/kg) were: 0 (control), 50, 100, 150, and 200. Carvacrol and cinnamaldehyde improved apparent metabolizable energy but did not change protein and ether extract digestibility. Supplementation increased intestinal villus height and villi:crypt ratio; in which 100 mg/kg produced the greatest villus height. Serum uric acid levels were lower in birds receiving supplementation. Improvement in the activity of glutathione peroxidase and glutathione-S-transferase was observed, while lower uric acid, thiobarbituric acid reactive substances, and reactive oxygen species levels were observed. Microencapsulated carvacrol and cinnamaldehyde improve apparent metabolizable energy and can be administered in broiler feed without risk to the bird’s health. These supplements may serve as alternative products to aid the performance of commercial poultry